2015
DOI: 10.1186/s41021-015-0009-5
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity-suppressing effect of aqueous extract of Connarus ruber cortex on cigarette smoke-induced micronuclei in mouse peripheral erythrocytes

Abstract: IntroductionAccording to published information, it has not been determined whether the inhalation of cigarette smoke can induce chromosome aberrations and/or point mutations in mice, though cigarette smoke is clearly carcinogenic to mice. We tested clastogenicity of inhaled cigarette smoke in mouse by a micronucleus test using peripheral erythrocytes. Since it is important to determine the in vivo anti-genotoxic effect against inhaled cigarette smoke to reduce the risk of tobacco carcinogenesis, we also tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The non-significant difference between the number of micronucleated immature erythrocytes in the bone marrow and the number of micronucleated erythrocytes in peripheral blood sample at GD 18 is explained by the theory stating that the spleen in mice does not remove micronucleated erythrocytes [43] .…”
Section: Discussionmentioning
confidence: 99%
“…The non-significant difference between the number of micronucleated immature erythrocytes in the bone marrow and the number of micronucleated erythrocytes in peripheral blood sample at GD 18 is explained by the theory stating that the spleen in mice does not remove micronucleated erythrocytes [43] .…”
Section: Discussionmentioning
confidence: 99%
“…C. ruber has been used as a folk remedy for several diseases, including diabetes in South America, and its extract is consumed as herbal tea. Previously, we reported that its extract decreased the level of DNA damage in the white blood cells of smokers [16] and prevented the induction of insulin resistance [17]. However, the underlying mechanism has not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%